Perencanaan Design Dan Analisa Anggaran Biaya Menggunakan Metode Bow Untuk Pembangunan Musholla Baitul Makmur - RIBANGUN BAMBAN JAKARIA; MOH.ARIF KURNIAWAN; MOCHAMMAD DIDIK DIANTONO; YUSUF KHOIRUDDIN (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The prayer room is a sacred building where Muslims hold worship. The building is relatively smaller than the mosque so its capacity can only accommodate a maximum of 50 people. The problem with the prayer room is that the prayer room will be built with limited funds because it is purely self-help and little is received from external assistance. So it is necessary to carry out preliminary planning that is related to the budget and cost allocation so that in the future the building does not stop in the middle of the road. This research aims to carry out cost planning so that the prayer room building is in accordance with the plan and the costs used do not exceed the existing costs. This research uses the BOW method, which is a method that provides a comprehensive framework for understanding and planning all aspects of development. The result of this research is to build a Baitul Makmur prayer room on empty land amounting to IDR 354,102,500. The budgeted costs include the cost of building foundations until they are completed so they can be used.